Comparative Analyses between Skeletal Muscle miRNAomes from Large White and Min Pigs Revealed MicroRNAs Associated with Postnatal Muscle Hypertrophy. - Xihui Sheng; Ligang Wang; Hemin Ni; Lixian Wang; Xiaolong Qi; Shuhan Xing; Yong Guo (PLoS ONE, 2016)
The molecular mechanism regulated by microRNAs (miRNAs) that underlies postnatal hypertrophy of skeletal muscle is complex and remains unclear. Here, the miRNAomes of longissimus dorsi muscle collected at five postnatal stages (60, 120, 150, 180, and 210 days after birth) from Large White (commercial breed) and Min pigs (indigenous breed of China) were analyzed by Illumina sequencing. We identified 734 miRNAs comprising 308 annotated miRNAs and 426 novel miRNAs, of which 307 could be considered pig-specific. Comparative analysis between two breeds suggested that 60 and 120 days after birth were important stages for skeletal muscle hypertrophy and intramuscular fat accumulation. A total of 263 miRNAs were significantly differentially expressed between two breeds at one or more developmental stages. In addition, the differentially expressed miRNAs between every two adjacent developmental stages in each breed were determined. Notably, ssc-miR-204 was significantly more highly expressed in Min pig skeletal muscle at all postnatal stages compared with its expression in Large White pig skeletal muscle. Based on gene ontology and KEGG pathway analyses of its predicted target genes, we concluded that ssc-miR-204 may exert an impact on postnatal hypertrophy of skeletal muscle by regulating myoblast proliferation. The results of this study will help in elucidating the mechanism underlying postnatal hypertrophy of skeletal muscle modulated by miRNAs, which could provide valuable information for improvement of pork quality and human myopathy.